2015
DOI: 10.1038/sj.bdj.2015.528
|View full text |Cite
|
Sign up to set email alerts
|

Maintaining dental implants – do general dental practitioners have the necessary knowledge?

Abstract: The present study confirmed that the current implant education at both undergraduate and postgraduate levels in the UK does not instil confidence to the GDPs to provide and maintain dental implants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…The issue of the life expectancy of dental implants is a notoriously difficult to define, being reportedly one of the most common misperceptions among patients (Yao et al 2017; Vipattanaporn et al 2019). At the same time, it is an issue that most clinicians were uncomfortable to express an opinion to their patients (Jayachandran et al 2015). As dentists are patients’ main source of information, unrealistic perceptions among dentists or their inability to provide clear information to patients on that issue could affect patients’ attitudes (Yao et al 2017; Kashbour et al 2018).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The issue of the life expectancy of dental implants is a notoriously difficult to define, being reportedly one of the most common misperceptions among patients (Yao et al 2017; Vipattanaporn et al 2019). At the same time, it is an issue that most clinicians were uncomfortable to express an opinion to their patients (Jayachandran et al 2015). As dentists are patients’ main source of information, unrealistic perceptions among dentists or their inability to provide clear information to patients on that issue could affect patients’ attitudes (Yao et al 2017; Kashbour et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The questionnaire consisted of 10 items on demographic data, 6 items surveying attitudes, 2 items on self-reported competence toward dental implant maintenance, and 17 items objectively testing competences and knowledge related to maintaining dental implants. The questions about attitudes were based on the work of Jayachandran (Lang-Hua et al 2013; Jayachandran et al 2015). Self-reported competence with implant maintenance allowed the dentists to state the scope of their competence among 4 options—from offering a comprehensive oral examination to implant maintenance care, treatment of problems and complications of implants, and referral of all patients with implants to other dentists.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding indicated the inadequacy of implant education in the entire dental education system. In a study by Jayachandran et al, 77% of general dentists were trained in only theoretical aspect of implant [11].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study from Britain confirmed that current implant education at both undergraduate and postgraduate levels does not instill confidence in general dental practitioners to provide and maintain dental implants. Of dentists who answered a evaluation sheet, 77% stated that they learned only theoretical aspects of dental implants during their undergraduate training.…”
Section: Educational Needs To Prevent and Control Implant Complicationsmentioning
confidence: 99%